The White Desert - Cooper, Courtney Ryley, 1886-1940; Fischer, Anton Otto, 1882-1962 (Salt Lake City, UT : Project Gutenberg, 2006)
"The White Desert" by Courtney Ryley Cooper is a novel written in the early 20th century. The story follows a young man named Barry Houston, who embarks on a challenging journey across the Rocky Mountains, heading to a place called Tabernacle. His venture into the treacherous terrain reveals a blend of internal conflicts and external obstacles, as he not only battles the harsh elements of nature but also grapples with secrets about his identity and circumstances. At the start of the book, Barry arrives in a small town named Dominion, where he is advised against attempting to cross Hazard Pass due to the dangers posed by the lingering winter weather. Undeterred, he fills his car with gas and sets off on his journey. As he navigates the perilous roads, he reflects on the joys and challenges that lie ahead. The narrative intertwines beautiful descriptions of nature with Barry's determination, which is mirrored by an underlying sense of mystery regarding his true purpose for the trip. The introductory chapters set a tone of adventure and introspection, promising an engaging mix of personal discovery and exploration amid the backdrop of the breathtaking yet hazardous western landscape. (This is an automatically generated summary.)
Release date is 2006-12-21
E-text prepared by Al Haines
Keywords: Railroad stories; Lumbering -- Fiction